Pelaksanaan Keterampilan Dasar Mengajar Guru Sosiologi pada Masa New Normal Di SMA N 1 Pasaman - Selvi Fauzia Selvi Fauzia; Marleni Marleni; Yanti Sri Wahyuni (STKIP PGRI Sumatera Barat, 2021)
This research was motivated by the Corona Virus Outbreak Pandemic (covid 19), Covid 19 was first reported in Indonesia on Monday 2 March 2020. This incident hampered all activities of human life from various sectors, especially in the field of education, namely teaching and learning activities. From the problems or phenomena found, of course there is a relationship and effort that must be made by sociology teachers to the implementation of the basic skills of teaching teachers with their students. The formulation of the research problem is how the basic skills of teaching sociology teachers in the new normal period at SMA N 1 Pasaman. The theory used in this research is the behavioristic theory proposed by B.F Skinner. This research approach is a qualitative approach with a descriptive type of research. The types of data in this research are primary and secondary data. There were 8 informants in this study. Data collection methods used are observation, in-depth interviews and document studies. To achieve the validity of research data using triangulation techniques. Meanwhile, the unit of data analysis used was the individual with data analysis by Miles and Huberman, namely data reduction, data presentation, data presentation and conclusion drawing. From the results of the study, it can be concluded that the implementation of the basic skills of teaching Sociology teachers in the New Normal period is very different from the pre-covid 19 period, all of which can be implemented. Based on the 5 skills that researchers observed, the implementation of these basic skills was not implemented in offline learning in the New Normal. Keywords: Basic Teaching Skill, Sociology Teacher, New Normal